Optimizing output spectral linewidth of fiber laser utilizing phase-shifted long-period fiber grating. (October 2021) - Jiao, Kerong; Shen, Hua; Yang, Feiyan; Wu, Xuecheng; Bian, Yinxu; Zhu, Rihong
Highlights: Utilizing phase-shifted long-period fiber grating (PS-LPFG) to optimize output spectral linewidth of high-power fiber laser. A detailed design philosophy and method of PS-LPFG was proposed, according to the characteristics of spectrum broadening. The PS-LPFG was fabricated by point-by-point scanning technique and dual annealing method. Alleviating the deterioration of laser spectral linewidth caused by nonlinear effect. Suitable for continuous-wave and pulsed fiber lasers with different structures. Abstract: Suppressing nonlinear effects in fiber laser by special fiber gratings has attracted growing attentions. Currently, most researches mainly focus on suppressing stimulated Raman scattering. However, the mitigation of the nonlinear effects, such as self-phase modulation or four wave mixing, which broaden the main lobe of the output laser spectrum has not been paid attention. We report a novel method for universally and conveniently optimizing output spectral linewidth of fiber laser by applying phase-shifted long-period fiber grating (PS-LPFG). A detailed design philosophy and method of PS-LPFG was proposed. Further, a symmetrical PS-LPFG was fabricated to verify the feasibility of the method. The central wavelength of the grating's passband was designed to match the signal light of a 1075 nm fiber laser. A 200 W continuous-wave oscillator was also established to evaluate the PS-LPFG's performance. Experimental results demonstrate that the spectral broadening of the main lobe is clearly alleviated. The 30 dB linewidth of the evaluation system is narrowed approximately 32.9% by the PS-LPFG. The 0.03 dB insertion loss of the fabricated grating avoids the deterioration of the signal laser's power. Furthermore, the 0.023 °C/W thermal slope of the grating allows for potential applications in higher power fiber lasers.